Development of E-LKPD based on learning style differentiation in economics subjects in class XI State High School in Surabaya - Kumalasari, Desi; Subroto, Waspodo Tjipto; Sakti, Norida Canda (Technium Social Sciences Journal, 2024)
The emergence of the development of an Android-based offline version of economic E-LKPD learning media with learning style differentiation aims to (1) analyze the feasibility of E-LKPD; (2) to analyze the practical structure of E-LKPD; (3) to analyze how big the change in student learning outcomes is before and after being exposed to the media that has been developed; 4) to analyze students' responses after using the media developed. The testing phase was limited to 4 students in each school, namely State High School 6 Surabaya, State High School 7 Surabaya State High School 13 Surabaya, State High School 15 Surabaya, and State High School 16 Surabaya. This research uses a 4D model (define, design, develop, disseminate). The research results were declared very feasible with a material test percentage of 100%, language test 90%, media test 100%. The media practicality level is 90%. 86% of students gave positive responses to this development media so that interactive learning media based on E-LKPD is suitable to support students' understanding and be applied in the learning process.